BINA GERAK UNTUK ANAK TUNA DAKSA - , NGUSMAN (Pendidikan Dasar, 2008)
Abstract : A movement need is a component movement organ consisting of  a muscle system, a bone system, a joint system, a nerve system. A normal movement is needed for a good movement, and a complete movement organ is also functionally good. If a movement undergoes a disturbance, this can happen because of an uncomplete movement organ or disfunctionally movement organ. The condition of  disable children are because of their brain defect which will much influence their muscle like flexid muscle or spastic, which make their slow joint movement or even no movement at all. For this problem, we need to give movement practice guidance as an effort to develop the rest of the students’ ability in oreder that they can adapt to their society     their slow joint movement